2020
DOI: 10.1111/jvim.15976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pimobendan on left atrial transport function in cats

Abstract: Background Arterial thromboembolism is a sequela of hypertrophic cardiomyopathy (HCM) in cats related to left atrial (LA) enlargement and dysfunction. Hypothesis Pimobendan improves LA transport function in cats. Animals Twenty‐two client‐owned cats with HCM and 11 healthy cats. Methods Prospective, double‐blind, randomized, placebo‐controlled clinical cohort study. Cats were randomized to receive either pimobendan (0.25 mg/kg PO q12h) or placebo for 4 to 7 days. Nineteen echocardiographic variables of LA size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 86 publications
(380 reference statements)
2
2
0
2
Order By: Relevance
“…We did not have enough data to assess if any medications received affected AAPSE, such as furosemide or pimobendan, which could have had an effect on LV preload and left atrial and LV systolic function, respectively, and thus an impact on AAPSE values. [46][47][48] In conclusion, we found that AAPSE was lower in cats with HCM, and cats with HCM stage C have the lowest values of AAPSE. This might be a new measurement of LV systolic performance, most likely related to longitudinally systolic function.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…We did not have enough data to assess if any medications received affected AAPSE, such as furosemide or pimobendan, which could have had an effect on LV preload and left atrial and LV systolic function, respectively, and thus an impact on AAPSE values. [46][47][48] In conclusion, we found that AAPSE was lower in cats with HCM, and cats with HCM stage C have the lowest values of AAPSE. This might be a new measurement of LV systolic performance, most likely related to longitudinally systolic function.…”
Section: Discussionsupporting
confidence: 47%
“…We did not have enough data to assess if any medications received affected AAPSE, such as furosemide or pimobendan, which could have had an effect on LV preload and left atrial and LV systolic function, respectively, and thus an impact on AAPSE values. 46 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…This parameter is widely used to assess contractility in several species [ 39 , 40 , 41 ]. The effects of pimobendan on inotropism appear less pronounced in anaesthetised dogs than in awake dogs [ 38 ]. In the present study, PV and MA were used to assess changes in inotropism: PV is the maximum velocity of blood in the aorta, and MA is the slope of the aortic velocity curve.…”
Section: Discussionmentioning
confidence: 99%
“…Аритмії виявляли лише у трьох (18 %). Згідно з дослідженнями авторів [19][20], наявність шуму в серці підвищує вірогідність гіпертрофічної кардіоміопатії у котів порівняно з тваринами без шуму.…”
Section: рис 2 ехокардіографія серця у кота 6 роківunclassified